Enhanced crystal formation of methylammonium lead iodide via self-assembled monolayers and their solvation for perovskite solar cells - Kittiwut Chaisan (2018)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. The quality of a perovskite photo-absorber layer is strongly dependent on the morphology of initially deposited PbI2 precursor film. In this work, surface modification of titanium dioxide (TiO2) substrates with self-assembled monolayers (SAMs) was performed to control the quality of the PbI2 and MAPbI3 perovskite layers. Two small organic molecules, each with a different backbone, 3-aminopropanoic acid (APA) and 4-aminobenzoic acid (ABA), were selected and their solvation effects were also investigated. Small homogeneously distributed cracks were found in the PbI2 film produced from the modification with APA molecules in demethyl sulfoxide or ethanol solution, whereas films produced from modification with ABA molecules showed different effects. These small cavities act as pathway for MAI intercalation and facilate PbI2-to-MAPbI3 conversion, leading to PbI2-free perovskite film. The different morphologies were caused by different adsorption behaviors of each SAM on the TiO2 surface. APA molecules interact with the hydroxyl groups of TiO2 while ABA molecules do not. Therefore, with APA treatment, the perovskite solar cells showed improvements in power conversion efficiency in comparison to either the devices without surface modification or ones treated with ABA molecules. The reasons behind the enhancement are attributed to longer charge carrier lifetime and better charge transfer at the TiO2/APA/perovskite interface. The results imply that the choice selected for SAMs and their solvents are crucial to obtaining high quality perovskite layers and efficient perovskite solar cells.